Japan's industrious revolution : Economic and social transformations in the early modern period - Hayami, Akira (Studies in Economic History, 2015)
The book examines Japan's 'industrious revolution' from the seventeenth to nineteenth centuries, showing how demographic change, household labor strategies, and rising work intensity laid the foundations for Japan's later industrialization.